Visitors’ Opinion and Preference about Ahsan Manzil, Old Dhaka: An Exploratory Study (Journal of Bangladesh Institute of Planners, 2012)
Ahsan Manzil, situated on the left bank of the river Buriganga, is one of the most significant heritage sites of Bangladesh. This site is one of the major sources of recreation for the inhabitants of Dhaka, particularly for the dwellers of the congested Old Dhaka. But the conservation of this invaluable heritage site and its management have always failed to receive proper attention of the concerned authorities. The current research mainly focuses on visitors’ characteristics and preferences for Ahsan Manzil and people’s willingness to pay for the attributes offered by this place. Selected socio-economic variables concerned with the tourists are tested for association with the frequency of visit using chi-square analysis. The priority attributes for visitors in choosing the Ahsan Manzil are analyzed using Analytic Hierarchy Process (AHP). Then some policy suggestions have been made in the study.Journal of Bangladesh Institute of Planners Vol. 5, Dec 2012, pp. 139-150